'We'll have what they're having', cultural identity through diet in the English Saxon Period. (February 2016) - Holmes, Matilda
Abstract : The roots of the English population lie in diverse cultural origins. Within the second half of the first millennium AD, there were two major migrations, firstly the Saxons in the immediate post-Roman period, and later following the 'Viking' incursions of the mid-9th century. This paper considers the visibility of these migrations in the animal economy. Zooarchaeological data from 141 Saxon sites within England were analysed for evidence of diet and animal husbandry. Results indicate that there were signatures specific to native British rural populations in the early Saxon phase, relying largely on a self-sufficient economy, consuming very few wild species or domestic birds. Saxon cultural differences were implied from a number of sites, dependant on the increased importance of cattle in the diet and as culturally symbolic animals signifying status and utilised for trade. There was also evidence for the earliest settlers to have used pigs as a 'mobile larder', to provide meat while they established herds and flocks of cattle and sheep. Regional differences were visible in the late Saxon phase, within Wessex and the Danelaw, related to agricultural changes in the midlands and central southern region, and cultural identity, particularly within the heartlands of the northern Danelaw, towards an increase in cattle production.